Wittgenstein, Frazer und die "ethnologische Betrachtungsweise." - Brusotti, Marco (Über Wittgenstein., 2014)
Wittgenstein wanted to adopt "a far-distant point of view" and look at philosophical problems from an ethnological perspective. Was his sharp confrontation with James Frazer's principal work, The Golden Bough: A Study in Magic and Religion, an exercise in such an "ethnological point of view?" In this study, Brusotti shows that Wittgenstein's thinking opened up new dimensions in language and cultural philosophy.